Trichomycterus santanderensis: A new species of troglomorphic catfish (Siluriformes, Trichomycteridae) from Colombia - Castellanos-Morales, Cesar A. (Zootaxa, 2007)
Trichomycterus santanderensis, described as a new species of troglomorphic catfish, was collected from the cave “El Puente” located in the upper Lebrija River basin of the Santander Department of northeast Colombia. The new species has light-red pigmentation, a first pectoral ray as long as the pectoral fin, and variable reduction in eye size. A comparative analysis with other troglomorphic species from South America and epigean species from northern Colombia is presented.